Analisis Strategi Komunikasi Pengelolaan Zakat, Infak dan Sedekah ( ZIS ) melalui Media Sosial (Studi Kasus Rumah Zakat Banda Aceh) - Rahmawati Rahmawati (IAIN Batusangkar, 2022)
This study aims to determine the communication strategy for the management of Zakat, Infaq and Alms (ZIS) through social media at Rumah Zakat Banda Aceh. social media at Rumah Zakat Banda Aceh.